Evaluation of Some Chemical and Sensory Properties of Processed Cheese Analogue with Selected Vegetable Oils (International Journal of Chemical and Process Engineering Research, 2015)
Cheese analogues are cheese-like products with varied compositions and functional properties which produced by partial or whole replacement of milk components, in particular milk fat, by non milk-based components. The purpose of this research was to evaluate the effect of replacement of milk fat in processed cheese with different formulations from olive, corn and sesame oils on some chemical and sensory properties. The results indicated that the peroxide values were not affected by the replacement of milk fat with vegetable oils significantly (P